Formulation development, stability and anticancer efficacy of core-shell cyclodextrin nanocapsules for oral chemotherapy with camptothecin - Ünal, Hale; Öztürk, Naile; Bilensoy, Erem (Beilstein Journal of Organic Chemistry, 2015)
Background: The aim of this study was to design and evaluate hybrid cyclodextrin (CD) nanocapsules intended for the oral delivery of the anticancer agent camptothecin (CPT) in order to maintain drug stability in the body and to improve its eventual bioavailability. For this reason, an amphiphilic cyclodextrin (CD) derivative per-modified on the primary face 6OCAPRO was used as core molecule to form nanocapsules with the nanoprecipitation technique. Nanocapsules were further coated with the cationic polymer chitosan to improve the cellular uptake and interaction with biological membranes through positive surface charge. Nanocapsules were evaluated for their in vitro characteristics such as particle size, zeta potential, drug loading and release profiles followed by cell culture studies with the MCF-7 and Caco-2 cell line evaluating their anticancer efficacy and permeability. The CD nanocapsules were imaged by scanning electron microscopy (SEM). The concentration of CPT entrapped in nanocapsules was determined by reversed phase HPLC. The in vitro release study of CPT was performed with a dialysis bag method under sink conditions mimicking the gastric and intestinal pH. The hydrolytic stability of CPT in nanocapsules was investigated in simulated gastric and intestinal fluids (SGF, SIF).Results: The mean particle sizes of both anionic and cationic CPT-loaded nanocapsules were in the range of 180–200 nm with polydispersity indices lower than 0.400 indicating monodisperse size distribution of nanocapsules with favourable potential for intracellular drug delivery to tumour cells. Surface charges of anionic and cationic nanocapsules were demonstrated as −21 mV and +18 mV, respectively. The stability of CPT in simulated release media, SGF and SIF were maintained suggesting the improved protection of the drug molecule from rapid hydrolysis degradation or gastrointestinal pH in nanocapsule oily core. Furthermore CD nanocapsules showed higher anticancer efficacy than CPT solution against the MCF-7 cell line. Permeation of CPT across Caco-2 cells was found to be 3 fold higher when incorporated in hybrid CD nanocapsules compared with a DMSO solution.Conclusion: Oral CD nanocapsules indicating increased oral bioavailability might be a promising strategy to maintain the physiological stability and to improve the oral bioavailability of problematic anticancer drugs such as CPT which may contribute to patient quality of life and drug efficacy in cancer therapy.
Keywords: amphiphilic cyclodextrin; camptothecin; core-shell; nanocapsule; oral chemotherapy